COVID-19–sensitive tumour response: 2-year assessment of the SARS-CoV-2 humoral response in cancer patients in oncology hospital in Poland - Piotr Kosiorek; Bożena Mikołuć; Samuel Stróż; Anna Hryniewicz; Dorota E. Kazberuk; Robert Milewski; Anna Grzeszczuk; Magdalena J. Borkowska; Anna Stasiak‐Barmuta (Cancer Immunology, Immunotherapy)
Abstract Vaccination has been considered the most crucial defence against viral infections, including SARS-CoV-2. Numerous reports have demonstrated the effectiveness of the above vaccines in oncological patients. It has also been proven that, apart from vaccinations and oncological therapy, the course of the cancer process itself influences the magnitude of the humoral response, especially in people after infection with SARS-CoV-2. The phenomenon we observe seems to confirm the presence of a "natural" defence potential in a cancer patient's body, in this case, directed against infection with a viral pathogen. A "stronger" antiviral response also explains the asymptomatic course of SARS-CoV-2 infection in some of the above patients. To what extent the SARS-CoV-2 infection weakened the "natural" potential of the anticancer response in these patients remains an open question. Objective This study aimed to answer the question about the impact of the cancer process on the humoral response in oncological patients vaccinated against SARS-CoV-2 infection and in patients after COVID-19. Material and methods One thousand six hundred and sixty-eight people were observed. Over 2 years, 5,082 SARS-CoV-2 IgG and IgM antibody samples were determined. The concentration of antibodies was assessed in groups of oncological patients: those undergoing anticancer therapy after contracting COVID-19 and those after vaccination against the SARS-CoV-2 infection. Results The obtained results indicate a naturally more significant humoral response in oncological patients who have not been vaccinated and have not undergone anticancer therapy, such as radiotherapy, chemotherapy, or surgical intervention. The above observation applies to patients with breast, lung, colon, kidney, and testicular cancer, although the response varies significantly depending on the type of cancer. Graphical abstract